Kinerja Cabinet Dryer pada Pengeringan Jahe Merah dengan Memanfaatkan Panas Terbuang Kondensor Pendingin Udara - Nunik Lestari; Samsuar Samsuar; Ervi Novitasari; Khaidir Rahman (Jurnal Agritechno, 2020)
Red ginger is rich in antioxidants and active ingredients, so the drying process should be carried out using low temperatures. Drying red ginger at low temperatures can be done using a cabinet dryer whose heating source comes from the wasted heat of the AC condenser. The purpose of this study was to test the performance of cabinet dryer with a heating source derived from the wasted heat of an AC condenser, on drying red ginger, and with several different levels of drying load. Performance testing was carried out with 600, 900, and 1200 grams of red ginger, which were then divided into 6 drying racks. Data observations and analyzes include drying temperature, relative humidity, moisture content, drying rate, heat used to increase material temperature, heat used to evaporate material water, energy requirements for the drying process, and energy efficiency. The results show that the cabinet dryer with a heating source from the wasted heat of the AC condenser is able to dry the red ginger to reach a moisture content of 9.24-10.71% in accordance with SNI standards, with a drying time of 6.5-8.7 hours. The energy used to dry red ginger ranges from 1281.67-2583.86 kJ. Drying efficiency achieves from each treatment ranges from 14.04-21.15%.